DETERMINANT FACTORS OF PURCHASE INTENTION FOR ZARA BRAND: CASE OF GENERATION Z - Budiono, Sidik; Wijaya, Felicia Fenny (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
The purpose of this paper aims to analyze the effects of country of origin, sensory perception, impulsive buying, fashion innovativeness to purchase intention and indirectly to perceived quality. The subjects of this study were 241 respondents who were born between 1997 - 2012 (generation Z) and has shopped from Zara. The method used in this research is quantitative research by taking samples with purposive sampling technique. Authors used Partial Least Square-Structural Equation Modelling for data analysis. The result of this study indicates that country of origin affects perceived quality. Fashion innovativeness affects purchase intention. Fashion innovativeness affects perceived quality. Impulsive buying affects purchase intention. Impulsive buying affects perceived quality. Perceived quality affects purchase intention. Sensory perception affects perceived quality. Country of origin moderates the effect of sensory perception to perceived quality is significant. Country of origin moderates the effect of fashion innovativeness to perceived quality is not significant. Country of origin moderates the effect of impulsive buying to perceived quality is not significant.